Molecular and morphological assessment of invasive, inland Rattus (Rodentia: Muridae) congenerics in South Africa and their reservoir host potential with respect to Helicobacter and Bartonella - Bastos, Armanda D.S. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.